The Kachin Ethno-Nationalism over Their Historical Sovereign Land Territories in Burma/Myanmar - Htung, Yaw (Thammasat Review, 2022)
Burma/Myanmar is a native home for various ethnic groups. Some of the larger ethnic groups–such as Burmese, Shan, Kachin, Karen, Mon, Rakhine, Karenni and Chin–strongly identifying with ethnic-based territories as “states”, while “regions” are typically dominated by the majority Burmese ethnic group. However, there are many other ethnic groups including minorities such as Rohingya, Palaung, Wa, Kokang, Lahu, Pa’O, Danu, Akha who have their individual territories within states and regions in Burma/Myanmar. In fact, Burmese ethno-nationalism has been deeply ingrained in the aspects of language, culture and religion since Burmese nationalists acting as national policy makers of the government have molded and continue to mold Burma/Myanmar into a Burmese nation state. Consequently, most of the larger ethnic groups have adopted similar mainstream ethno-nationalism based on their ethnicities in order to demand their political right. Accordingly, Kachin ethno-nationalism has politically engendered the Kachin self-determination struggle over their historical sovereign land territories. This study thus focuses on Kachin ethno-nationalism and their self-determination, which is in part the political imbroglio of Burma/Myanmar. In this study, grounded theory was applied as the research methodology. Grounded theory involves developing theories or concepts based on the perspectives of the research findings in terms of a bottom-up approach, rather than hypotheses. Hence, the research process was a simultaneous process of data collection and analysis, which included field informants, key informants and in-depth interviews. As a result, the research findings reveal that the Kachin ethno-nationalism has evolved from the notion of Kachin ethnicity so as to demand the right to rule themselves over their historical sovereign land territories entitled as the Kachin state and the Kachin sub-state. As a central moot point, the study argues that the Kachin ethno-nationalism and its ethnicity have been a tandem catalyst that the Kachins take up to struggle for political autonomy and ethnic equality in Burma/Myanmar.